Pengaruh Beban Kerja, Kompensasi Non Finansial, dan Disiplin Kerja Terhadap Kinerja Pelayanan Pegawai - Dedek Syahputri; Taufiq Risal (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the influence of workload, non-financial compensation, and work discipline on employee service performance. The research method used is a quantitative approach with multiple linear regression analysis. Based on the results of the first hypothesis test, it was found that workload has a positive and significant effect on service performance, indicating that a proportional and well-managed workload can encourage employees to deliver more optimal service. The second hypothesis test shows that non-financial compensation has a negative and significant effect on service performance, suggesting that the forms of non-financial rewards currently implemented may not be well-targeted or aligned with employee expectations, thus negatively impacting their performance. Meanwhile, the third hypothesis test indicates that work discipline does not have a positive and significant effect on employee service performance. However, simultaneously, the F-test results show that workload, non-financial compensation, and work discipline together have a positive and significant effect on service performance, with an F-value of 31.333 and a significance level of 0.000. These findings provide important implications for management in designing strategies to improve service performance through the effective management of internal.